1969
DOI: 10.1002/oms.1210020607
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐impact studies—XLVII: The mass spectra of 2‐aryl‐1,3‐dithianes and ‐1,3‐dithiolanes

Abstract: The fragmentation patterns in the spectra of 2-aryl-l,3-dithianes and -1,3-dithiolanes have been elucidated by deuterium labelling studies. Ortho effects are observed in the spectra of 2(o-alkoxyphenyl)-l,3-dithianes. The molecular ions of the 1,3-dithianes eliminate SZH. and metastable peaks substantiate these eliminations. The hydrogen involved in this elimination randomises ((2-4, 5 and 6) prior to elimination in the spectrum of 2-phenyl-l,3-dithiane, but originates mainly from C-5 in that of the bis propan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Similar losses are observed from the molecular ions of 1,3,5-trithiane' and 2-phenyl-1 ,3-dithiane. 5 The loss of S,H. from 2-phenyl-l,3-dithiane involves the hydrogens at the 4,5 and 6 positions, and we have suggested1r5 that this could either be due to partial hydrogen scrambling or to enhanced loss of the hydrogen from the 5-position.…”
Section: 'mentioning
confidence: 88%
“…Similar losses are observed from the molecular ions of 1,3,5-trithiane' and 2-phenyl-1 ,3-dithiane. 5 The loss of S,H. from 2-phenyl-l,3-dithiane involves the hydrogens at the 4,5 and 6 positions, and we have suggested1r5 that this could either be due to partial hydrogen scrambling or to enhanced loss of the hydrogen from the 5-position.…”
Section: 'mentioning
confidence: 88%
“…R = Ph, R' = p-MeOC6H4) enhances, following reaction [2], the rapid rearrangement of the series 4 product according to eq. [4]. Thus, when R = R' = aryl, only products of series 6 are isolated by room temperature manipulations.…”
Section: Resultsmentioning
confidence: 99%
“…130°C, eq. [4]; the products that result from formal [1,3] sigmatropic shifts have been isolated and characterized as the trisubstituted alkenes 6a-6c. Although we have not made a detailed study of the rates of rearrangement of 4a-4c, it is clear from the observed reaction times (see experimental section) that 46 and 4c rearrange more readily than does 4a.…”
Section: Resultsmentioning
confidence: 99%
“…The isomer (12) showed spectral data almost superimposable with the pulvinate obtained from isopinastric acid (lo), prepared as outlined in Scheme 1. It is worth mentioning that during these studies we found that the most practical route to the Qthenvise difficultly accessible benzoylformate (15) first prepared from 3,4,5trimethoxyphenylacetonitrile by the methods outlined previ0us1y.l~ Thus, condensation between the phenylacetonitrile and diethyl oxalate gave ethyl 3-cyano-3-(3,4,5-trimethoxy)pyruvate (16) which was converted into the cinnamate (17). Treatment of the cinnamate with acid [under conditions controlled to avoid demethylation of the 4-OMe group to give (19) 15] then led to the anhydride (18) which by reduction with lithium aluminium hydride gave the (the corresponding 2-methoxy-derivative was also prepared) was from 4-methoxybenzaldehyde following conversion into the dithian ( 13), metallation and carboxylation to ( 14), esterification, and finally removal of the dithian protecting group with CuII salts in acetone-water.…”
Section: Syntheses Of Permethylated Derivatives Of Pinastric Acid And...mentioning
confidence: 99%